Comparison of characteristic computed tomographic findings of gastrointestinal and non-gastrointestinal stromal tumors in the small intestine - Inoue, Akitoshi; Ota, Shinichi; Sato, Shigetaka; Nitta, Norihisa; Shimizu, Tomoharu; Sonoda, Hiromichi; Tani, Masaji; Ban, Hiromitsu; Inatomi, Osamu; Ando, Akira; Kushima, Ryoji; Murata, Kiyoshi (Abdominal imaging, 2019)
Purpose We aimed to reveal specific findings of gastrointestinal stromal tumors (GISTs) in the small intestine on contrast-enhanced computed tomography (CT) by comparing GISTs with non-GISTs. Methods We enrolled 28 patients with 39 GISTs and 20 patients with 22 non-GISTs who underwent enterectomy with a preoperative diagnosis of small intestinal tumor. All lesions were diagnosed by histopathological examination. Two radiologists independently evaluated internal homogeneity, growth pattern, calcification, intratumoral hemorrhage, degeneration, ulceration, and lymphadenopathy and measured the maximum diameter of the tumor and contrast-enhanced CT (CECT) value of the solid portion as well as the diameter and CT value of the feeding artery and drainage vein on CECT in the arterial and venous phases. Results Intratumoral hemorrhage was seen in 15.4% and 25.6% of GISTs and in 0% and 0% of non-GISTs ( p = 0.079 and 0.010), with good interobserver agreement ( κ = 0.715). The drainage vein diameter correlated well with the maximum diameter of the tumor ( r = 0.744, p < 0.001). The CT value of the solid tumor part in the arterial and venous phases ( p < 0.01) and the CT value of the drainage vein in the arterial phase ( p < 0.05) were higher for GISTs than for non-GISTs ( p < 0.01). Conclusions Strong parenchymal enhancement with the peak in the arterial phase and the CT value of the drainage vein in the arterial phase was characteristics findings of GIST compared with non-GISTs. The diameter of the drainage vein was proportional to the maximum diameter of GISTs.